Correction: Corrigendum: p-wave triggered superconductivity in single-layer graphene on an electron-doped oxide superconductor - A. Di Bernardo (Nature Portfolio, 2017)
Nature Communications 8: Article number: 14024 (2017); Published: 19 January 2017; Updated: 1 March 2017 The present address for U. Sassi is incorrect in this Article. This author does not have a present address. The correct full affiliation details for this author are given below: Cambridge Graphene Centre, University of Cambridge, Cambridge CB3 0FA, UK.